538 Research on clinical‐paraclinical and evolutive aspects in patients with post spinal cord injury (SCI) statuses and Covid‐ 19 – a systematic literature review (Balneo and PRM Research Journal, 2024)
Abstract: The COVID‐19 pandemic has generated a lot of interest among doctors as well as scientistsaround the world. Studies on the impact of the Covid‐19 pandemic, including in people with postSCI sufferance, are ongoing, aiming to understand the pathophysiological mechanisms of SARS‐CoV2 in target tissues, to optimize related methods of diagnosis and treatment in both, initial andlater phases of the disease – e.g.: ”long Covid” status – and thus, to make a substantial contributionto the quality of life improvement of the affected patients.After using the Preferred Reporting Items for Systematic Reviews and Meta‐Analyses (acronymPRISMA) method to quest for afferent knowledge, it resulted a quite small number (12) of articles,most of them indirectly approaching this topic. Therefore, is important to deepen this niche – whichis scarcely approached – in order to find new therapeutic approaches able to combat COVID‐19‐associated to SCI manifestations – like, for instance, to check whether the principle of intermittenthypoxia treatment is effective and worth to be included in the rehabilitation treatment protocols –as neither an indubitable effective drug or vaccine, or respectively, cure for SCI, has been providedso far.Keywords: Spinal cord injury, Paraplegia, Tetraplegia, COVID‐19, intermittent hypoxia treatment